STUDI KOMUNITAS GASTROPODA DI PERAIRAN PASANG SURUT DESA HUTUMURI KECAMATAN LEITIMUR SELATAN KOTA AMBON - Benjamin Mornaten (BIOPENDIX, 2019)
Background: Ecologically, gastropods have an important role to control the population of macroalgae in coral reefs, and economically the snail shell can be used as a source of income for people, especially coastal communities. Method: The method used is a quadratic linear transect method that is placed perpendicular to the coastline with a combination of plots on the transect line. Data analysis included species composition, diversity, dominance, and evenness of gastropod species. Results: The results of the study were 1549 gastropod individuals consisting of 46 species of 23 genera, 17 families, 2 subclasses and 4 orders. In general, the diversity and abundance of gastropods in the coastal tidal waters of the hutumuri village are relatively moderate and the species dominance is evenly distributed. Conclusion: Which consists of 46 species, 21 genera, 17 families and 4 orders. Ecological parameters of the gastropod community in the tidal waters of Hutumuri Village are density value (0.97 ind/m2), abundance value (12.867 in/m) important value (0.2590), diversity value (3.0468), dominance value (0,1445), the value of harmony (0.8010). Dominant index value (D) (0.1445) indicates no species dominance. The diversity pattern of gastropod species in the tidal waters of Hutumuri Village is having a uniform distribution pattern.